Keratoplasty indications and outcomes: The experience of a tertiary health center in Southeastern of Turkey - Balsak, Selahattin; Yildiz Ekinci, Dilbade (Annals of Medical Research, 2021)
Aim: The study aims to report the indications of keratoplasty surgeries and our surgical outcomes performed in our hospital that provides tertiary health care.Materials and Methods: This retrospective study was conducted analyzing the files of the patients undergone keratoplasty for optical, therapeutic and tectonic purposes between 2014-2018. The patients’ age, gender, indication for keratoplasty, preoperative and postoperative best-corrected visual acuity and surgical technique preferred, whether graft rejection developed or not during postoperative follow-ups, treatments administered to the patients developed rejection and follow-up periods were recorded.Results: The study included 200 eyes of 174 patients undergone keratoplasty. Of the eyes 180 (90%), 13 (6.5%) and 7 (3.5%) received corneal transplantation for optical purpose, for tectonic/therapeutic purpose and for cosmetic purpose respectively. The mean follow-up period was 21.7±6.2 months (range 6-48 months). Of the eyes 78 (39%), 40 (20%), 25 (12.5%), 19 (9.5%), 16 (8%), 11 (5.5%), and 9 (4.5%) were operated due to infectious/non-infectious corneal scar, pseudophakic/aphakic bullous keratopathy, graft failure/rejection, corneal dystrophy, keratoconus, keratitis/abscess and spontaneous corneal perforation respectively. Forty (20%) of the eyes developed allograft reaction. At the end of the study period, 50 (25%) eyes could not maintain graft transparency. The most common causes of inability to maintain graft transparency were endothelial failure and allograft reaction.Conclusion: Keratoplasty is an important and effective surgical method that increases visual acuity in blindness conditions caused by corneal diseases.Keywords: Cornea; graft survival; keratoplasty.